Percutaneous intervention for diffuse pulmonary arteriovenous malformations by occlusion of large lobar pulmonary arteries - Greyling, Adele; Pepeta, Lungile (SA Heart Journal, 2018)
We present a case of an 8-year-old girl with bilateral, diffuse, lower lobe pulmonary arteriovenous malformations (PAVMs). These were initially treated by selective embolisation of the feeder arteries with coils and vascular plugs. Due to unsatisfactory results (persistent cyanosis and diffuse residual PAVMs), prolonged procedure time, high contrast dose and the fact that she was declined surgical resection by cardiothoracic surgery as she was perceived to be a high anaesthetic risk and surgical resection was presumed to be complex; a staged approach for occlusion of the left and right lower lobar pulmonary arteries with large vascular plugs was chosen.